2015
DOI: 10.1590/s1806-92902015000300005
|View full text |Cite
|
Sign up to set email alerts
|

Models of protein and amino acid requirements for cattle

Abstract: -Protein supply and requirements by ruminants have been studied for more than a century. These studies led to the accumulation of lots of scientific information about digestion and metabolism of protein by ruminants as well as the characterization of the dietary protein in order to maximize animal performance. During the 1980s and 1990s, when computers became more accessible and powerful, scientists began to conceptualize and develop mathematical nutrition models, and to program them into computers to assist w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 51 publications
2
36
0
3
Order By: Relevance
“…The values of protein content per kg EBW were similar to those found by other authors in cattle in the same weight range (SANT'ANA et al, 2011;TEDESCHI et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The values of protein content per kg EBW were similar to those found by other authors in cattle in the same weight range (SANT'ANA et al, 2011;TEDESCHI et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Soybean is one of the vegetables that contain protein with reasonably balanced amino acid composition, and it is a protein source used to balance diets for cattle (TEDESCHI et al, 2015). Many soybean byproducts are used in ruminant diets, such as the bran, meal, cake and oil.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made at quantifying microbial N production (MicN) in dairy diets (Fox et al, 2004;Huhtanen and Hristov, 2009;Broderick et al, 2010). A series of evaluations of microbial protein predictions have also been undertaken (Bateman et al, 2001;Yu et al, 2003;Tedeschi et al, 2015). Although these exercises have been useful, few have evaluated the role of rumen carbohydrate digestibility on MicN flow based on actual carbohydrate digestibility (ruminal or total-tract), whereas other evaluations assumed that book or predicted digestibility values for feeds are accurate and unbiased .…”
Section: Introductionmentioning
confidence: 99%
“…From the nutritive utility point of view, the protection of protein (to avoid ruminal fermentation) needs to be conducted to optimize protein utilization in the post rumen digestive tract of bulls (Aboozar et al, 2013). For this reason, besides feeding bulls with degraded proteins in the rumen (to maximize rumen microbial protein), it is important to provide the undegraded protein supplement (called rumen undegraded protein [RUP] or rumen-protected protein) in the rations to increase the supply of amino acids for bulls (Tedeschi et al, 2015;Kumar et al, 2018). In the case of RUP, Prasetiyono et al (2007) has found the SOYXYL as one of the rumenprotected protein supplements derived from extruded Soybean (Glycine max), which is beneficial for fattening of beef cattle.…”
Section: Introductionmentioning
confidence: 99%